Research on Software Defined Storage Technology for the Next-Generation Data Center - Zhenzheng Sun; Jing Gong; Yong Duan; Junzhi Lei (Dianxin kexue)
With the rapid development of internet technology and the explosive growth of data, the storage system tightly coupled hardware and software design is limiting the development of storage technology severely, and unable to meet the rapidly changing needs in the mobile internet and big data era increasingly. Software defined storage as a new storage system architecture is more suitable for the development of the next-generation data centers. The SDS research status was described, started from the definition of SDS, and then SDS reference architecture combined with the SDS system requirements was proposed, finally the evolution of ideas were put forward.